Prevalence of Obstructive Sleep Apnea in Type 2 Diabetes - Dhakal, Sobodh Sagar; Maskey, Robin; Mishra, Nabin Kumar; Karki, DB (Journal of Diabetes and Endocrinology Association of Nepal, 2019)
Introduction: Diabetes are common disorder that often coexist as they have similar risk factors including obesity. As 10% increase in weight accelerates the risk of OSA by 10%it is not surprising to see both disorder in the patient.Methods: All the patients who attended to our sleep clinic in OM Hospital and Research Centre were asked about diabeteic history. Those who are already diagnosed as diabetics and on medications or diet control were enrolled into the study. STOP BANG questionnaire was used to categorize the patients for probable obstructive sleep apnea.Results: Among 67 patients who underwent diagnostic polysomnography 22 patients had normal AHI, 19 had intermittent snoring and rest had normal diagnostic polysomnography. Among 45 patients 5 had predominantly central sleep apnea and 40 had obstructive sleep apnea.Conclusion: In our study that OSA is very common in patients with Type 2 diabetes and worse glycaemic control is a high index of suspicion and sleep history especially for OSA should be included in all the patients of type 2 diabetes. Any patients with uncontrolled diabetes despite medications independent of obesity should be screened for OSA.